Cryptosporidiosys and it’s implications in public health - Kalman I. (Medicamentul Veterinar)
Cryptosporidiosys is considered by some authors as among the first three-four most important entheropathogens in humans. Humans can be contaminated true infected food or water, by inobservance of minimal hygiene conditions and by contact with infected animals. The prevention of the disease can be made through general ways, known by the majority of the population as minimal hygiene and sanitary conditions.